Front Matter Jurnal TRI DHARMA MANDIRI Volume 2 Nomor 1 - Yunita, S.Farm., M.Farm.Klin. (Scopus ID : 57213688462 (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2022)
-